PERSEPSI GURU TERHADAP PENGGUNAAN INTERACTIVE FLAT PANEL PADA MATERI PETA PEMBELAJARAN IPS KELAS V SEKOLAH DASAR - Siska Delia; Siti Aisyah; Shelia; Dina Syafifah; Fayed Muhamad Akbar; Susi Ratna Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to examine how teachers at SDN 05 Sembilan Koto perceived the use of Interactive Flat Panels (IFP) in social studies instruction, particularly with regard to map materials for Grade V students. A qualitative descriptive strategy was used in the study. Non-participatory observation and in-depth interviews with principals and classroom instructors were used to gather data. The findings showed that instructors' opinions of the use of IFP in map learning were favorable. Instructors saw IFP as a cutting-edge, successful, and captivating teaching tool that greatly increased students' motivation and engagement. tudents were able to grasp geographic concepts more dynamically and concretely because to the incorporation of IFP into map study. Instructors reported that IFP promoted a student-centered learning environment and helped to deliver lessons more effectively. Some difficulties were noted, nevertheless, such as the requirement for ongoing institutional assistance for hardware maintenance, sporadic connectivity problems, and the lack of technical training for teachers. Overall, the results show that IFP improves social studies education at the elementary school level and that maximizing its advantages depends on teachers' proficiency with digital technology.